Uncertainty modeling in knowledge engineering and decision making : Proceedings of the 10th International FLINS Conference - Kahraman, Cengiz; Kerre, Etienne E.; Bozbura, Faik Tunc (World Scientific proceedings series on computer engineering and information science, 2012)
This book presents the proceedings of the 10th FLINS conference, originally focused on Fuzzy Logic and Intelligent Technologies in Nuclear Science, now broadened to Computational Intelligence for applied research. It features state-of-the-art studies and developments in computational intelligence systems. Both theoretical foundations and practical applications are explored. The contributions reflect current advances and innovations in the field.